Investigation of Flavonoids as inhibitors of human DNA topoisomerase IIa - Vicente, Marta Raquel Fernandes (2019)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2019